Electrosynthesis of three-dimensional nanoporous nickel on screen-printed electrode used for the determination of narirutin in citrus wastewater - Beluomini, Maísa Azevedo [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Boldrin, Maria Valnice [UNESP] (Elsevier, 2021)
In this study, an electrochemical sensor was designed for the detection of narirutin using three-dimensional nanostructured porous nickel on screen-printed electrode (3DnpNi/SPE). The modified electrode was successfully synthesized by the dynamic hydrogen bubble template method. The 3DnpNi/SPE was characterized by spectroscopic, microscopic, and electrochemical methods. The results showed that the 3DnpNi/SPE presents good electrocatalytic activity for the oxidation of narirutin. The quantification of narirutin was conducted by differential pulse voltammetry, which showed a wide concentration range (1.0 × 10-7 – 1.0 × 10-5 mol L-1), with low detection limit (3.9 × 10-8 mol L-1), and excellent sensitivity (0.31 A L mol−1). The proposed electrode was applied toward the determination of narirutin in yellow water sample from the citrus industry, where it presented a good degree of accuracy. The 3DnpNi/SPE showed repeatability, long-term stability, and selectivity. The results obtained showed agreement with those obtained by HPLC/DAD method. Chemical compounds studied in this article.
Keywords: D(+)-Glucose (PubChem CID: 107526); D-fructose (PubChem CID: 5984); Differential pulse voltammetry; Electrochemical detection; Hesperidin (PubChem CID: 10621); Nanostructure; Naringenin (PubChem CID: 932); Narirutin; Narirutin (PubChem CID: 442431); Nickel chloride hexahydrate (PubChem CID: 11791229); Yellow water